Multifunctional microbeads for drug delivery in TACE. (1st September 2016) - Bannerman, Dawn; Wan, Wankei
ABSTRACT: Introduction : Transarterial chemoembolization (TACE) is the standard treatment for unresectable intermediate-stage hepatocellular carcinoma (HCC). Microbeads used to embolize tumor vasculature have recently been designed to deliver a therapeutic drug to the tumor site. Increasing the functionality of microbeads for TACE has the potential to improve therapy by accomplishing multiple, beneficial tasks with one system. Areas covered : Microbead functions beyond embolization and drug delivery that could be highly advantageous include detection and tracking with imaging, targeting, degradation, and the delivery of multiple therapeutics or combination therapies. This review covers the concepts of TACE for treatment of HCC, the need for controlled delivery systems and the use of drug-eluting beads. Shortcomings of the current technology and the current approaches to improve materials used as embolic microbeads are discussed. Relevant studies aimed to enhance microbead visibility, targetability, degradability, and the use of multiple therapeutics or combination therapies are reviewed. Expert opinion : The incorporation of nanoparticles that possess desirable properties into the microbead matrix is a suitable method of creating multifunctional microbeads. The development of these 'nano-on-micro' systems is a promising approach to improve TACE therapy and may lead to improved treatment.